Gone but not for garden - Collins, Kate, 1951- (Collins, Kate, 1951- Goddess of Greene St. mysteries., 2023)
When her cousin, an emcee at a local fashion show, is accused of murder, flower-shop owner Abby Knight teams up with Athena Spencer, whose family owns a garden center, to dig up the dirt on a growing list of suspects to weed out a killer.